Standards of reporting for MRI-targeted biopsy studies (START) of the prostate: recommendations from an international working group - Moore, Caroline M.; Kasivisvanathan, Veeru; Eggener, Scott; Emberton, Mark; Fütterer, Jurgen J.; Gill, Inderbir S.; Grubb III, Robert L.; Hadaschik, Boris; Klotz, Laurence; Margolis, Daniel J. A.; Marks, Leonard S.; Melamed, Jonathan; et al. (European urology, 2013)
Background - A systematic literature review of magnetic resonance imaging (MRI)-targeted prostate biopsy demonstrates poor adherence to the Standards for the Reporting of Diagnostic Accuracy (STARD) recommendations for the full and transparent reporting of diagnostic studies. - Objective - To define and recommend Standards of Reporting for MRI-targeted Biopsy Studies (START). - Design, setting, and participants - Each member of a panel of 23 experts in urology, radiology, histopathology, and methodology used the RAND/UCLA appropriateness methodology to score a 258-statement premeeting questionnaire. The collated responses were presented at a face-to-face meeting, and each statement was rescored after group discussion. - Outcome measurements and statistical analysis - Measures of agreement and consensus were calculated for each statement. The most important statements, based on group median score, the degree of group consensus, and the content of the group discussion, were used to create a checklist of reporting criteria (the START checklist). - Results and limitations - The strongest recommendations were to report histologic results of standard and targeted cores separately using Gleason score and maximum cancer core length. A table comparing detection rates of clinically significant and clinically insignificant disease by targeted and standard approaches should also be used. It was recommended to report the recruitment criteria for MRI-targeted biopsy, prior biopsy status of the population, a brief description of the MRI sequences, MRI reporting method, radiologist experience, and image registration technique. There was uncertainty about which histologic criteria constitute clinically significant cancer when the prostate is sampled using MRI-targeted biopsy, and it was agreed that a new definition of clinical significance in this setting needed to be derived in future studies. - Conclusions - Use of the START checklist would improve the quality of reporting in MRI-targeted biopsy studies and facilitate a comparison between standard and MRI-targeted approaches.
Gesehen am 31.05.2021